Understanding Elderspeak: An Evolutionary Concept Analysis. Issue 3 (3rd July 2021) - Shaw, Clarissa A; Gordon, Jean K
Abstract: Background and Objectives: Elderspeak is an inappropriate simplified speech register that sounds like baby talk and is used with older adults, especially in healthcare settings. Understanding the concept of elderspeak is challenging due to varying views about which communicative components constitute elderspeak and whether elderspeak is beneficial or harmful for older adults. Research Design and Methods: Rodgers' evolutionary concept analysis method was used to evaluate the concept of elderspeak through identification of elderspeak's attributes, antecedents, and consequences. A systematic search using the PubMed, CINAHL, PsycINFO, and Embase databases was completed. Results: Eighty-three theoretical or research articles from 1981 to 2020 were identified. Elderspeak characteristics were categorized by semantic, syntactic, pragmatic, paralinguistic, and nonverbal attributes. The primary antecedent to elderspeak is implicit ageism, in which old age cues and signs of functional or cognitive impairment led to simplified communication, usually from a younger caregiver. Research studies varied in reporting whether elderspeak facilitated or interfered with comprehension by older adults, in part depending on the operational definition of elderspeak and experimental manipulations. Exaggerated prosody, a key feature of elderspeak, was found to reduce comprehension. Elderspeak was generally perceived as patronizing by older adults and speakers were perceived as less respectful. In persons with dementia, elderspeak also increases the probability of resistiveness to care, which is an important correlate of behavioral and psychological symptoms of dementia. Discussion and Implications: Based on this concept analysis, a new definition of elderspeak is proposed, in which attributes that have been found to enhance comprehension are differentiated from those that do not. Recommendations for consistent operationalization of elderspeak in future research are made.